2016
DOI: 10.1016/j.pec.2016.08.004
|View full text |Cite
|
Sign up to set email alerts
|

Cancer patients’ understanding of longitudinal EORTC QLQ-C30 scores presented as bar charts

Abstract: Knowledge about patients' understanding of graphically displayed QOL results contributes to creation of optimal evidence-based feedback on the patients' present QOL and its trajectory.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
28
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(29 citation statements)
references
References 20 publications
1
28
0
Order By: Relevance
“…For example, McNair et al found accuracy rates ranging from 85% to 98% across six formats in a sample of 192 patients. Others found similar percentages . Interpretation in our study seemed to be most accurate when using a bar chart compared to a line graph, although it should be said that one particular figure using a line graph (ie aggregated PROMs scores over time with results of two treatment options) was also accurately interpreted.…”
Section: Discussionsupporting
confidence: 42%
See 1 more Smart Citation
“…For example, McNair et al found accuracy rates ranging from 85% to 98% across six formats in a sample of 192 patients. Others found similar percentages . Interpretation in our study seemed to be most accurate when using a bar chart compared to a line graph, although it should be said that one particular figure using a line graph (ie aggregated PROMs scores over time with results of two treatment options) was also accurately interpreted.…”
Section: Discussionsupporting
confidence: 42%
“…Others found similar percentages. 23,43,44 Interpretation in our study seemed to be most accurate when using a bar chart compared to a line graph, although it should be said that one particular figure using a line graph (ie aggregated PROMs scores over time with results of two treatment options) was also accurately interpreted. Therefore, it seems to depend partly on the type of information presented, which format was associated with better comprehension.…”
Section: Discussion Of Findingsmentioning
confidence: 67%
“…Development of thresholds for PRO measures has been recommended in the literature because the interpretation of scores on abstract metrics has been identified as one of the major barriers to the use of PRO measures in daily clinical practice [30]. The TCIs for the EORTC CAT Core can be integrated into software used for routine PRO monitoring to improve graphical presentation of PRO results (e.g., use of color-coding or reference lines [31,32]). In addition, TCIs make PRO scores more actionable and support the linking of PRO results to clinical decision-making [33,34].…”
Section: Discussionmentioning
confidence: 99%
“…Of 18 studies that met our inclusion criteria (Figure 1), 9 used mixed methods, [43][44][45][46][47][48][49][50][51] 7 used quantitative descriptive methods, [52][53][54][55][56][57][58] 1 used qualitative methods, 59 and 1 used a quantitative randomized controlled design 60 (Table 1). Ten of 18 studies met all MMAT criteria (Supplementary Table S2).…”
Section: Resultsmentioning
confidence: 99%
“…Study participants included patients (n ¼ 9), 43,45,46,48,49,51,54,56,58 providers (n ¼ 4), 44,50,55,60 or both (n ¼ 5) 47,52,53,57,59 (Table 1). Sample sizes were 10 to 548 patients and 3 to 233 providers.…”
Section: Study and Symptom Characteristicsmentioning
confidence: 99%